Electrocatalytic Oxidation of Hydroxide Ions by Co3O4 and Co3O4@SiO2 Nanoparticles Both at Particle Ensembles and at the Single Particle Level. Issue 5 (11th March 2020) - Xie, Ruo‐Chen; Volokhova, Maria; Boldin, Aleksei; Seinberg, Liis; Tsujimoto, Masahiko; Yang, Minjun; Rasche, Bertold; Compton, Richard G.
Abstract: We report that the Co3 O4 nanoparticle‐mediated electrochemical oxidation under alkaline conditions of the hydroxide ion on a glassy carbon macroelectrode leads to hydrogen peroxide as the initial oxidation product of electron transfer. The latter is inferred to subsequently partially decompose to dioxygen by catalytic chemical reaction at the nanoparticles. At the single particle level, electrochemical particle‐electrode impacts point out the rate‐determining step and the limiting kinetics of the reaction. Furthermore, particles with a core‐shell structure of a Co3 O4 core and SiO2 shell are synthesised, and their electrochemical behaviour is studied and compared with bare Co3 O4 nanoparticles, suggesting the very likely broken or highly porous state of the silica shell, which is not otherwise easily distinguished, for example, by electron microscopy. Abstract : A critical look at the interface : Co3 O4 nanoparticle‐mediated electrochemical oxidation of hydroxide ions on a glassy carbon macroelectrode under alkaline conditions leads to hydrogen peroxide as the initial oxidation product of electron transfer. The latter is inferred to subsequently partially decompose to dioxygen by catalytic chemical reaction at the nanoparticles. Furthermore, the observed similar electrochemical behaviour of two types of nanoparticles, bare Co3 O4 and Co3 O4 ‐core SiO2 ‐shell, suggests the very likely broken or highly porous state of the silica shell.